Head-worn displays and job content: A systematic literature review. (February 2021) - Bal, Michiel; Benders, Jos; Dhondt, Steven; Vermeerbergen, Lander
Abstract: Despite the emergence of head-worn displays at work around forty years ago, few studies have appeared about their impact on job content. To investigate this, a systematic literature review was conducted on these devices and job content, defined as job demands and controls. In total, 3481 studies were identified using five scientific databases. After applying selection criteria, reference searches, citation tracking and an in-depth reading, 28 studies were selected for review. Remarkably, the findings of these studies showed contrasting results. Both increases and decreases in job demands and controls were identified. We distinguished across studies two opposite approaches for the deployment of these devices, i.e. a supportive and a directive approach. Highlights: The use of HWDs shows contrasting results for job content, in terms of both job demands and job controls. We identified a supportive and a directive approach for the deployment of HWDs. These approaches are related to the nature of the tasks as well as their organizational embeddedness.